The Effects of Process Conditions on Reliability of Silicon Nanowires - Uchechukwu C. Wejinya; Nathan Willems; Zhuxin Dong; Mojtaba Abolhassani (Nanomaterials and Nanotechnology)
Material reliability is among the crucial factors that impact the performance of devices. In order to predict material reliability, an accelerated ageing study to predict material shelf life when subjected to temperature and humidity was performed on silicon nanowires (SiNWs). We investigated the effects of process conditions on the diameter and the quality of SiNWs using Atomic Force Microscopy followed by statistical analysis. The experimental results revealed that diameter of SiNWs has a linear relationship with changing temperature and humidity. These results are of significant importance and will be a critical design consid‐ eration for the manufacture of nanoelectromechanical systems involving SiNWs.